ОБМОРОКИ — МЕЖДИСЦИПЛИНАРНАЯ ПРОБЛЕМА - Г. Н. Гороховская; О. П. Николин; В. Л. Юн; Е. С. Соколова (Архивъ внутренней медицины, 2013)
Syncope today is a multi-disciplinary problem. Syncope is the most common consequence of the defeat of cardio - vascular system, organic or functional CNS endocrine system. In clinical practice are not rare cases when syncope is the first and only manifestation of a disease. However, syncope can occur in the absence of organic disease in apparently healthy people. The complexity of the pathogenetic mechanisms underlying the development of syncope, a combination of different mechanisms in the same patient, the treatment of patients in the interictal period, the lack of awareness of physicians lead to late diagnosis of the true cause of syncope, the incorrect treatment of this group of patients, which further leads to a decrease in quality of life patients with syncope, in poor prognosis in these patients.